Thermal and Mechanical Analysis of Polyvinyl Chloride (PVC) to Polyethylene (PE) Bonding via Friction Stir Spot Welding Process - Omar Hassan Hameed; Mahmood Mohammed Hamzah; Mursal Luaibi Saad; Ghaith Rabeea Abduljabbr; Azher S Barrak; Yasir W. Abduljaleel (Journal of Techniques)
This study investigates the thermal and mechanical behavior of friction stir spot welding (FSSW) for joining dissimilar thermoplastics, Polyvinyl Chloride (PVC) and Polyethylene (PE). Given the inherent differences in polarity, crystallinity, melting temperatures, and surface energies, bonding between PVC and PE presents significant challenges. The experimental work involved applying FSSW under varying process parameters (rotational speed and dwell time), followed by tensile shear testing and infrared-based thermal analysis. The results revealed that the rotational speed had a dominant effect on peak interfacial temperature, reaching up to 137°C, which exceeds the crystalline melting range of both materials (PVC: 75–105°C; PE: 130–135°C), facilitating localized melting, which promotes effective molecular inter diffusion at the weld interface. Taguchi-based DOE analysis confirmed that optimal parameters (1700 RPM and 2 min dwell) produced the highest joint strength and temperature. Tensile shear strength results also indicated that appropriate heat input and tool interaction facilitated robust bonding without external adhesives or surface treatments. This research offers valuable insights into optimizing polymer-to-polymer welding conditions, paving the way for scalable, environmentally friendly joining methods suitable for packaging, automotive, and biomedical applications.